Solidarity and Power in Linguistic Choice of Tidar University Students’ Interaction - Sri Wulandari; Linda Eka Pradita; Rahma Ade Triana; Ilmi Nurin Nafiatur Rizqoh (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study is about linguistic choice made by university students, mainly Tidar University students, when they need to interact with other interlocutors on campus. Accordingly, it aims to investigate the linguistic choice patterns done by Tidar University students. This research is delimited to a social factor in Sociolinguistics, namely participants/addressee, which is further subdivided into two specific aspects, namely solidarity and power. Mixed-method research design is employed through self-reported open-ended questions. There are 198 fifth-semester students from five faculties at Tidar University involved as respondents. To collect the data, self-report questionnaires adapted from Cohn and Ravindranath (2013) were distributed. Then, the results were analysed using Holmes’s (2013) framework of social factors. The findings reveal that in high-solidarity interactions, such as with close friends, there are 40,82% students used Javanese. In contrast, when solidarity reduces, like with distant senior students, respondents tend to switch to Bahasa Indonesia or a mix codes (vernacular and Bahasa Indonesia). Distinct from solidarity aspect, when respondents encounter interlocutors with higher perceived power, Bahasa Indonesia becomes the primary choice for interaction and the percentage reaches almost 100%. Conversely, with less than 10% of the respondents utilize Javanese when they interact with cleaning staff and security personnel. Ultimately, results substantiate that the patterns of linguistic choice within a single domain, namely university, can be diverse because of the dynamics of solidarity and power which are implicitly manifested in everyday student interactions on campus.